1-V Mixed-Mode Universal Filter Using Differential Difference Current Conveyor Transconductance Amplifiers - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz (My University, 2024)
This paper presents a mixed-mode universal filter using differential difference current conveyor transconductance amplifiers (DDCCTA). Despite using a minimum number of MOS differential pairs, the proposed DDCCTA is a multiple-input, multiple-output device, that was achieved using the multiple-input bulk-driven MOS transistor (MIBD-MOST) technique, multiple-output current followers and transconductance gains. A subthreshold technique is used to achieve minimum power consumption of the DDCCTA. Thanks to the multiple-input and multiple-output of DDCCTA, the mixed-mode universal filter based on the proposed element can realize five standard filter responses, i.e., low-pass, high-pass, band-pass, band-stop, and all-pass responses, of four modes, i.e., voltage-mode, current-mode, transadmittance-mode, and transimpedance-mode, thus providing 194 filter responses from a single circuit. The natural frequency and quality factor of the filter response can be controlled electronically and orthogonally. The proposed DDCCTA and mixed-mode universal filter are simulated and designed using 0.18 μm CMOS technology to confirm the functionality of the new circuit. The mixed-mode universal filter uses ±0.5 V of supply voltage and consumes 0.374 mW of power when operating at a natural frequency of 10 kHz.
Keywords: active filter; analog integrated circuit; bulk-driven MOS transistor; differential difference current conveyor transconductance amplifier; low-voltage low-power